2019
DOI: 10.4274/haseki.galenos.2019.4922
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antiepileptic Drug Treatment on Thyroid Hormone Levels in Epilepsy Patients

Abstract: Aim: Antiepileptic drugs (AEDs) can have an effect on hormone metabolism and function, and alter serum levels of some hormones. This study aimed to determine the effects of AEDs on thyroid function test results in epilepsy patients. Methods:The study included 82 epilepsy patients aged 18-45 years. Serum free thyroxin (fT4), free triiodothyronine (fT3), and thyroidstimulating hormone (TSH) levels were measured in all the participants. Thyroid hormone levels in subgroups were investigated. In addition, Serum AED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…A previous study showed similar findings with Carbamazepine. 20 There are several possible explanations for this association, including more seizure activity and/or longer duration of AED exposure. Patients with a longer duration of epilepsy are more likely to have a higher seizure burden, which may have a negative impact on thyroid hormone homeostasis, especially through the hypothalamus and TSH.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed similar findings with Carbamazepine. 20 There are several possible explanations for this association, including more seizure activity and/or longer duration of AED exposure. Patients with a longer duration of epilepsy are more likely to have a higher seizure burden, which may have a negative impact on thyroid hormone homeostasis, especially through the hypothalamus and TSH.…”
Section: Discussionmentioning
confidence: 99%